1976
DOI: 10.1093/infdis/133.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cytosine Arabinoside, Adenine Arabinoside, and 6-Azauridine on Rabies Virus in Vitro and in Vivo

Abstract: The antiviral agents cytosine arabinoside, adenine arabinoside, and 6-azauridine were shown to inhibit the replication of rabies virus in vitro but not the replication of Sindbis virus. These same drugs were not effective in reducing the mortality rate in mice challenged with street rabies virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1976
1976
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The outcome of human rabies is invariably fatal, and there is no effective treatment, despite the fact that some investigators have tried several drugs [10,11]. Two out of the three patients at AUBMC received Ara-C, following reports about its usefulness in itro against the replication of rabies virus [12,13], but both of them died.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of human rabies is invariably fatal, and there is no effective treatment, despite the fact that some investigators have tried several drugs [10,11]. Two out of the three patients at AUBMC received Ara-C, following reports about its usefulness in itro against the replication of rabies virus [12,13], but both of them died.…”
Section: Discussionmentioning
confidence: 99%
“…This in vitro inhibitory effect of ara-C on virus replication was partly reproduced in another study, in which viral replication was only slightly decreased, even in conditions completely shutting down host DNA synthesis [152]. Another pyrimidine analog inhibitor, 6-azauridine (6-azu), was shown to have an antiviral effect on laboratory-adapted RABV strain replication in vitro [155] that was unlikely to be due to a direct virucidal effect [151]. However, neither of these drugs was effective at reducing the mortality rate in mice challenged with non adapted virus strains [155].…”
Section: /115mentioning
confidence: 86%
“…However, cytarabin (also known as cytosine arabinoside or ara-C) is a potent inhibitor of DNA synthesis that has surprisingly been shown to be effective in vitro against the replication of laboratory-adapted RABV strains [153][154][155]. It has been suggested that this inhibition occurs soon after infection (3 hours post-infection) [153][154] and is specific to this molecule, as other pyrimidine nucleoside analogs or derivatives (such as 2-thio and 5-iodo derivatives of ara-C and uracil arabinoside) have no inhibitory effect [154].…”
Section: /115mentioning
confidence: 99%
See 2 more Smart Citations